Pengembangan Media Interaktif "DIDAYA" (Mading Budaya Kaltara) sebagai Pengenalan Budaya pada AUD - Hasfaraini, Ari Rahmi; Kusumawati, Kusumawati; Apriliyana, Nur Pangesti; Maolana, Aldo; Leban, Firda Yunias (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
There are various cultures that can be introduced to early childhood, such as introducing the diversity of tribes, races, religions, customs and others. Therefore, it is very important for the rest to be introduced to this diverse culture from an early age, so that the next generation still knows their own culture. Early childhood (AUD) is the next generation of the nation and has a high absorption capacity, it is very important to introduce the culture around them. However, the current situation, the lack of children's knowledge about their own culture. The cause is the lack of APE related to the introduction of culture in schools. Therefore, this study seeks to develop interactive media as an introduction to culture to early childhood. The development of this interactive media is important to do because diversity is an extraordinary wealth that must be accepted, maintained, and used as a tool to unite the nation. This study uses the Research and Development (R&D) method with the Borg and Gall model with the results of expert validation of material and media feasibility obtained an ideal of 82% included in the very good category and the results of users reaching a percentage of 90% with a very good category. Therefore, with thw existence of DIDAYA, it is hoped that at the early childhood education level, teachers will find it easier to introduce the local culture around the children in a more enjoyable way.Ada berbagai ragam budaya yang dapat dikenalkan pada anak usia dini, seperti mengenalkan keberagaman suku, ras, agama, adat istiadat dan lain-lain. Maka dari itu, sangat penting bagi sisa untuk dikenalkan dengan budaya yang beragam ini sejak dini, agar generasi penerus tetap mengenal budayanya sendiri. Anak usia dini (AUD) adalah generasi penerus bangsa dan memiliki daya serap yang tinggi, sangat penting untuk mengenalkan budaya disekitarnya. Namun, keadaan sekarang ini, minimnya pengetahuan anak mengenai budaya mereja sendiri. Penyebabnya adalah kurangnya APE yang berkaitan dengan pengenalan budaya yang ada disekolah. Oleh karena itu, penelitian ini bertujuan untuk mengembangkan media interaktif sebagai pengenalan budaya kepada anak usia dini. Pengembangan media interaktif ini penting untuk dilakukan karena keberagaman adalah kekayaan luar biada yang harus diterima, dipelihara, dan digunakan sebagai alat untuk mempersatukan bangsa. Penelitian ini menggunakan metode Research and Development (R&D) dengan model Borg and Gall dengan hasil validasi ahli materi dan kelayakan media diperoleh keidealan 82% termasuk dalam kategori sangat baik dan hasil dari pengguna mencapai persentase 90% dengan kategori sangat baik. Oleh karena itu, dengan adanya DIDAYA ini diharapkan pada jenjang PAUD guru-guru lebih mudah mengenalkan budaya yang ada disekitar anak dengan lebih menyenangkan